Editorial - Restrepo López, Natalia (Cuadernos de Administración, 2023)
The 75th issue of Cuadernos de Administración falls in the January-April 2023 quarter. The Six articles published in this issue result from the journal's commitment to keeping a permanent call for papers, seeking to promote continuous scientific dissemination, and following the highest quality standards. In this issue, authors from various countries and regions of Colombia have submitted their manuscripts to our editorial process. The journal and its editorial committee would like to thank the reviewers who contributed to evaluating each article by their experience, knowledge, and commitment. The Six papers on this issue result from exhaustive research processes to resolve various administrative and organizational sciences questions. The first article is "The impact of the technologies of the Fourth Industrial Revolution -4RI- on human talent in SMEs in Bogota". In this article, the authors diagnose the adoption of the fourth industrial revolution technologies and their impact on human talent in SMEs in Bogota. This diagnosis is carried out using an analysis model based on three main axes: impact, enablers, and perception, the latter being a Minimum Viable Product (MVP) as a result. The paper "Tourist typologies likely to Contribute to the Economic and social resilience of Palermo - Huila" analyzes the influence of the possible patterns of the tourist plan in sustainable development management in the municipality of Palermo, Huila, after the pandemic. This is achieved by analyzing information from primary and secondary sources. The third paper in this issue, entitled "Human talent management in a public university from its institutional regulations," analyzes human talent management in a public university by characterizing the elements contemplated in the institutional regulations. The authors find that human talent management is defined as a set of integrated processes designed to attract, develop, motivate, and retain the employees of this institution. The fourth article in this issue is "Knowledge Management and Partnership Management Capacity: A Literature Review." This article describes knowledge management and partnership management capacity concepts according to the scientific literature and Ministry of Science, Technology, and Innovation guidelines. Our issue ends with two review papers, the first of which is entitled "Proposal of Indicators for urban agriculture territorial planning." It seeks to substantiate a proposal of indicators for urban agriculture planning that contributes to sustainability and food sovereignty in Cuba. The proposed indicators make it possible to diagnose and characterize urban agriculture in a territory, establish relationships between its main components from a territorial perspective, and define planning criteria and actions. The second article, "Leadership and its Influence on Happiness at Work: a narrative review of the Literature," describes the relationship between happiness at work and leadership. This description is based on a narrative review of the literature available in the Scopus and Web of Sciences databases. The review encompasses general debates, review of previous studies, state-of-the-art analysis, and research perspectives to broaden the discussion on the relationship between these two variables and their influence on organizational performance".